The Influence of Managerial Support and Organizational Justice on Employee Performance: A Case Study at PT Pratama Abadi Industri-JX - Anggraeni, Lola; Astuti, Winda Dwi (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to analyze the influence of managerial support and organizational justice on employee performance at PT Pratama Abadi Industri-JX, a shoe manufacturing company. In today's competitive business environment, management support and organizational justice perceptions have become crucial factors in enhancing employee productivity. This research employed a quantitative approach using survey methods with 24 respondents randomly selected from 130 company employees. The research instrument consisted of questionnaires developed based on managerial support indicators (Sorongan et al., 2015), organizational justice indicators (Lestiyanie & Yanuar, 2019), and employee performance indicators (Adhari, 2020). Data were analyzed using descriptive statistics and multiple linear regression with SPSS software. Validity and reliability tests showed that all research instruments were valid and reliable (Cronbach's Alpha = 0.833). The Kolmogorov-Smirnov normality test confirmed normal data distribution (Sig. = 0.057 > 0.05). Multiple regression analysis results indicated that managerial support and organizational justice simultaneously have a positive and significant influence on employee performance (F = 10.143, Sig. = 0.001 < 0.05) with R² value of 0.491, meaning 49.1% of employee performance variation can be explained by both independent variables. These findings provide practical implications for PT Pratama Abadi Industri-JX management to enhance managerial support and create a fair organizational climate as strategies for improving employee performance.